GM-CSF Exhibits Anti-Inflammatory Activity on Endothelial Cells Derived from Chronic Venous Disease Patients - Tisato, Veronica; Secchiero, Paola; Rimondi, Erika; Gianesini, Sergio; Menegatti, Erica; Casciano, Fabio; Zamboni, Paolo; Zauli, Giorgio (Mediators of Inflammation, 2013)
Twenty patients affected by chronic venous disease (CVD) in tertiary venous network and/or saphenous vein were analyzed before surgical ablation by echo-color-doppler for the hemodynamic parameters reflux time (RT) and resistance index (RI), a negative and a positive prognostic factor, respectively. RT and RI were next correlated with relevant in vitro parameters of venous endothelial cells (VEC) obtained from surgical specimens, such as cell migration in response to serum gradient, proliferation index, intercellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1 expression, as well as cytokines release. Of interest, ICAM-1 expression in patient-derived VEC cultures correlated positively with RT and negatively with RI. Moreover, RT showed a positive correlation with the baseline osteoprotegerin (OPG) expression by VEC and an inverse correlation with VEC proliferation index. On the other hand, RI correlated positively with TNF-related apoptosis inducing ligand (TRAIL) expression. Among the cytokines released by VEC, GM-CSF showed a positive correlation with VEC proliferation and TRAIL expression and a negative correlation with OPG, ICAM-1 and VCAM-1 expression. Since in vitro recombinant GM-CSF induced VEC proliferation and counteracted the induction of ICAM-1, VCAM-1 and OPG upon exposure to TNF-α, our data suggest an anti-inflammatory activity of GM-CSF on venous endothelial cells.